2018
DOI: 10.3390/nu10070830
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity Effects of Ginsenoside Rg1 on 3T3-L1 Preadipocytes and High Fat Diet-Induced Obese Mice Mediated by AMPK

Abstract: Ginsenosides Rg1 is one of the major pharmacologically active saponins in ginseng, which as an antioxidant reduces oxidative damage in the liver and can also be used to prevent cardiovascular diseases and diabetes. However, there is no research targeting the effect of lipid metabolism in high-fat diet (HFD)-induced mice. In this study, we evaluated the anti-obesity effects of Rg1 in 3T3-L1 adipocyte cells and HFD-induced obese C57BL/6J mice. Administration of Rg1 to HFD-induced obese mice significantly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 48 publications
1
55
0
1
Order By: Relevance
“…Vitamin D relieves fat deposition in C2C12 cells through AMPK/SIRT1 [29]. Ginsenosides Rg1 reduces fat deposition in adipose tissue and 3T3-L1 cells by activating AMPK [34]. Aged Oolong Tea reduces fat deposits caused by a high-fat diet by activating AMPK [35].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D relieves fat deposition in C2C12 cells through AMPK/SIRT1 [29]. Ginsenosides Rg1 reduces fat deposition in adipose tissue and 3T3-L1 cells by activating AMPK [34]. Aged Oolong Tea reduces fat deposits caused by a high-fat diet by activating AMPK [35].…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Oxidative phosphorylation refers to the production of excessive oxygen-free radicals resulting in oxygen-free radicals and related metabolism by the excessive aggregation of products in the mitochondria. [44][45][46] Due to the overproduction of ROS or the imbalance in the antioxidant system, the cells could be damaged, especially the biological macromolecules, such as lipids, proteins, and nucleic acids. These cells would attract more macrophages and then cause the release of proinflammatory cytokines, which would conversely aggravate oxidative stress and eventually lead to obesity.…”
Section: F I G U R Ementioning
confidence: 99%
“…Adipocytes are highly specialized cells and can be generated from inducing preadipocytes in the involvement of a series of adipogenic transcription factors and enzymes [8]. It has been demonstrated that several adipogenic transcription factors including PPARγ, C/EBP family (C/EBPα, β, γ), and SREBP-1c can induce adipocyte differentiation (adipogenesis) [7]. Among them, PPARγ, considered as a master regulator for adipocyte differentiation, mainly expressed in adipose tissue and is both necessary and sufficient for adipocyte differentiation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The roles of C/EBP family members in adipogenesis were also interrupted. The activation of C/EBPα was found to be beneficial for enhancing insulin sensitivity in adipocytes [9], and the activation of C/EBPβ and C/EBPγ can stimulate the expression of PPARγ and C/EBPα [8,11], which can further regulate the expression of SREBP-1c and downstream adipocyte-specific proteins involved in lipolysis [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation